We need to use slope-intercept form, which is y = mx + b, where m is the slope and b is the y-intercept.

Slope is the change in y divided by the change in x. Given the two points, we can find the difference in the y-coordinates and divide that by the difference in the x-coordinates:

m = (-11 – (-1)) / (-2 – 2) = -10 / (-4) = 5/2

Now, we have:

y = (5/2)x + b

Substitute one of the given points for x and y to solve for b:

## Answers ( )

Answer:

y = (5/2)x – 6

Step-by-step explanation:

Slope: (-1 – -11)/(2 – -2)

10/4

5/2

y = (5/2)x + c

-1 = (5/2)(2) + c

-1 = 5 + c

c = -6

y = (5/2)x – 6

Answer:y = (5/2)x – 6

Step-by-step explanation:We need to use slope-intercept form, which is y = mx + b, where m is the slope and b is the y-intercept.

Slope is the change in y divided by the change in x. Given the two points, we can find the difference in the y-coordinates and divide that by the difference in the x-coordinates:

m = (-11 – (-1)) / (-2 – 2) = -10 / (-4) = 5/2

Now, we have:

y = (5/2)x + b

Substitute one of the given points for x and y to solve for b:

-1 = (5/2) * 2 + b

-1 = 5 + b

b = -1 – 5 = -6

The answer is

y = (5/2)x – 6.